2006
DOI: 10.1096/fj.05-5223com
|View full text |Cite
|
Sign up to set email alerts
|

Peroxynitrite induces Alzheimer‐like tau modifications and accumulation in rat brain and its underlying mechanisms

Abstract: To investigate the upstream effector that led to tau hyperphosphorylation, nitration, and accumulation as seen in Alzheimer's disease brain, and the underlying mechanisms, we bilaterally injected SIN-1, a recognized peroxynitrite donor, into the hippocampus of rat brain. We observed that the level of nitrated and hyperphosphorylated tau was markedly increased in rat hippocampus 24 h after drug administration, and these alterations were prevented by preinjection of uric acid, a natural scavenger of peroxynitrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
0
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(47 citation statements)
references
References 75 publications
6
39
0
2
Order By: Relevance
“…In contrast to wild type neurons, the viability of truncated tau bearing neurons has been decreased up to the half under the stress. This finding supports the idea that truncated tau could amplify the damage induced by oxidative stress, which was shown to impair neuronal functions (Butterfield et al 2006;Zhang et al 2006).…”
Section: Discussionsupporting
confidence: 88%
“…In contrast to wild type neurons, the viability of truncated tau bearing neurons has been decreased up to the half under the stress. This finding supports the idea that truncated tau could amplify the damage induced by oxidative stress, which was shown to impair neuronal functions (Butterfield et al 2006;Zhang et al 2006).…”
Section: Discussionsupporting
confidence: 88%
“…More information is available on nitration of cytoskeletal proteins in pathological processes where a correlation between this post-translational modification and cytoskeletal dysfunction is strongly suggested. Actin has been found heavily nitrated in a mouse model of amyotrophic lateral sclerosis [36] and in sickle cell disease [38], nitrated tau with an unordered secondary structure is described in Alzheimer's [39], nitrotyrosine incorporated in alpha-tubulin alters microtubule assembly and organization in cellular injury [40], abnormal alphasynuclein aggregation and nitration has been found in the frontal cortex in Pick's disease [41] and effects of nitration on the structure and aggregation of alphasynuclein have been described in vitro [42]. Moreover, one of the intermediate filaments, NF-L, was found to be particularly susceptible to nitration in vivo in sporadic amyotrophic lateral sclerosis and further observations revealed that NF-L nitration is a ubiquitous occurance in neurones suggesting that NF-L might function as a sink for free reactive nitrating species [37].…”
Section: Discussionmentioning
confidence: 99%
“…37 In brief, the rat hippocampi were quickly dissected out and homogenized on ice in buffer containing 50 mmol/L TrisHCl (pH 7.5), 150 mmol/L NaCl, 1% (v/v) Triton X-100, 1% (w/v) deoxycholate, 0.1% (w/v) SDS, 10 mmol/L NaF, 1 mmol/L Na 3 VO 4 , and 2 g/ml each of aprotinin, leupeptin, and pepstatin. Then, the hippocampal extracts (about 500 g total proteins) was immunoprecipitated with antipT668-APP at 4°C and shaken overnight, and then protein G agarose (Pierce Chemical Company, Rockford, IL) was added and incubated at 4°C for 2 hours.…”
Section: Immunoprecipitationmentioning
confidence: 99%